THE CHALLENGES OF TEACHING AND LEARNING ENGLISH FACED BY THE ENGLISH TEACHERS AND STUDENTS DURING COVID-19 PANDEMIC AT SMP PGRI BAREMBENG - Nurul Husna Amalia; Haryanto Atmowardoyo; Amirullah Abduh (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The aims of this research are to find out the teacher’s challenges in teaching English and the student‟s challenges in learning English at junior high school during pandemic dealing with learning English online. This research uses qualitative method. The data of this research were collected through questionnaire and interview. The subjects of this research were the teacher who teaches at second grade and the second-grade students at SMP PGRI BAREMBENG that was consisted 30 students which were taken by using random sampling. The result of data analysis found that (1) there are some challenges faced by the teacher in teaching English online at second grade students including, student‟s interest and enthusiasm in learning English online, difficulty in using ICT, difficulty in providing and explaining learning material, difficulty in measuring student‟s improvement and achievement and assessing student‟s work, (2) there are some challenges faced by the students at second grade including less enthusiastic (student‟s interests and motivation), difficulty in the learning process, and the lack of internet package and internet network.